Plasma Nitrate Levels Are Related to Metabolic Syndrome and Are Not Altered by Treatment with DPP-4 Inhibitor Linagliptin: A Randomised, Placebo-Controlled Trial in Patients with Early Type 2 Diabetes Mellitus - Melanie Reijrink; Stefanie A. De Boer; Anniek M. Van Roon; Riemer H. J. A. Slart; Bernadette O. Fernandez; Martin Feelisch; Hiddo J. L. Heerspink; Harry Van Goor; Jan-Luuk Hillebrands; Douwe J. Mulder (MDPI AG, 2021)
The depletion of nitrate and nitrite, stable nitric oxide (NO) end-products, promotes adipose tissue dysfunction and insulin resistance (IR). Dipeptidyl peptidase-4 (DPP-4) inhibitors have the potentially beneficial side effect of increasing NO availability. In this study, nitrate and nitrite levels and the effects of DPP-4 inhibitor linagliptin were investigated in relation to metabolic syndrome (MetS) markers. Treatment-naive patients with early type 2 diabetes mellitus (T2DM) (n = 40, median age 63 IQR (55-67) years, 63% male, mean HbA1c 45 ± 4.4 mmol/mol) were randomized (1:1) to linagliptin (5 mg/day) or placebo. MetS-related markers (body mass index (BMI), triglycerides, HOMA-IR, gamma-glutamyltransferase (GGT), C-reactive protein (CRP), and adiponectin), plasma levels of nitrate, nitrite, total free thiols (TFT) and vegetable intake were estimated at baseline and after 4 and 26 weeks of treatment. Plasma nitrate, but not nitrite, correlated positively with vegetable intake (r = 0.38, p = 0.018) and was inversely associated with HOMA-IR (r = −0.44, p = 0.006), BMI (r = −0.35, p = 0.028), GGT (r = −0.37, p = 0.019) and CRP (r = −0.34, p = 0.034). The relationship between nitrate and HOMA-IR remained significant after adjusting for BMI, CRP, vegetable intake and GGT. With stable vegetable intake, nitrate and nitrite, TFT, adipokines and CRP did not change after 26 weeks of linagliptin treatment. While plasma nitrate is inversely associated with MetS, linagliptin treatment does not significantly influence nitrate and nitrite concentrations, oxidative stress, adipose tissue function and systemic inflammation.